The ever-after bird - Rinaldi, Ann (Great episodes, 2007)
In 1851, thirteen-year-old Cecilia has her eyes opened to the horrors of slavery when she accompanies her ornithologist uncle on an expedition in search of the rare "Scarlet Ibis," and watches as he shows slaves the way to the Underground Railroad.